Ergodic stationary distribution of stochastic virus mutation model with time delay - Juan Ma; Shaojuan Ma; Xinyu Bai; Jinhua Ran (AIMS Mathematics, 2023)
The virus mutation can increase the complexity of the infectious disease. In this paper, the dynamical characteristics of the virus mutation model are discussed. First, we built a stochastic virus mutation model with time delay. Second, the existence and uniqueness of global positive solutions for the proposed model is proved. Third, based on the analysis of the ergodic stationary distribution for the model, we discuss the influence mechanism between the different factors. Finally, the numerical simulation verifies the theoretical results.